RESEARCH ON THE COMPETITIVE PERFORMANCE OF THE BULGARIAN NATIONAL TEAM OF UNDER - 16 FEMALE PLAYERS IN THE EUROPEAN CHAMPIONSHIP, DIVISION B IN 2012 - Tsanko Tsankov; Jasmine Tsankova (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
In today's basketball, the opinion that achieving high and stable sports results can be realized only by science-based long-term preparation is gaining more and more popularity. A major part of this preparation is the participation of adolescent female players in European Championships for the respective age group. The purpose of this study is to analyze the competitive performance of the Bulgarian National basketball team, consisting of female players up to 16 years of age, who took part in the European Championship, Division B, held in Tallinn, Estonia from 12 to 22 July 2012. For the purpose of the study information was gathered on the gaming performance of the players of the national team in all 9 played matches, comparing them by 16 indicators. The unit of observation of this study was the single game. The team competitive efficiency is a combination of the gaming performance of all players involved in the basketball game, regardless of the time that they were actually playing in the match. After analyzing the surveyed indicators, the following conclusions were made and those need to be the ground for the future education and training program of the researched national team, namely: increased activity in shooting from the two-point and three-point lines; increasing the effectiveness of the shooting from the two-point line and the free throws; improved ability to pass accurate (in space, time and effort) assists; improving the technique of blocking in defense and offense; improving the quality and the aggressiveness in defense play, which would increase the number of steals, but not at the expense of increased number of fouls.